Measles Virus Antibody in Cerebrospinal Fluids from Patients with Multiple Sclerosis - Salmi, A. A. (1972)
A strong measles-specific gel precipitation reaction was found in the cerebrospinal fluid (C.S.F.) of two patients with multiple sclerosis (M.S.) (total of 15 tested). The serum and C.S.F. specimens from these two patients were tested for measles antibody by six assay methods. The results were compared with those obtained from serum and C.S.F. specimens of a patient with subacute sclerosing panencephalitis (S.S.P.E.). The gel precipitation line produced by the C.S.F. from the M.S. patients was identical with one of the three lines produced by the C.S.F. from the S.S.P.E. patient. The main antigenic component responsible for measles antibody appearing in the C.S.F. of the S.S.P.E. patient and the M.S. patients was also electrophoretically similar, and the corresponding antibody was associated with IgG. The serum/C.S.F. antibody titre ratios with the various assay methods used suggest that the C.S.F. antibodies are mainly to other than envelope components of measles virus. No complement-fixing antibody against 27 other viruses or Mycoplasma pneumoniae was found in the C.S.F. of the two M.S. patients.